Candidates for non-pulsating stars located in the Cepheid instability strip in the Large Magellanic Cloud based on Strömgren photometry. Issue 3 (1st August 2019) - Narloch, Weronika; Pietrzyński, G; Kołaczkowski, Z; Smolec, R; Górski, M; Kubiak, M; Udalski, A; Soszyński, I; Graczyk, D; Gieren, W; Karczmarek, P; Zgirski, B; et al.
ABSTRACT: We present candidates for non-pulsating stars lying in the classical Cepheid instability strip based on the Optical Gravitational Lensing Experiment (OGLE) photometric maps combined with Strömgren photometry obtained with the 4.1-m Southern Astrophysical Research (SOAR) telescope, and Gaia Data Release 2 data in four fields in the Large Magellanic Cloud. We selected 19 candidates in total. After analysis of their light curves from OGLE surveys we found that all these stars appear to be photometrically stable at the level of a few mmag. Our results show that non-pulsating stars might constitute to about 21\!-\!30 per cent of the whole sample of giant stars located in the classical instability strip. Furthermore, we identified potential candidates for classical Cepheids with hot companions based on their Strömgren colours.